2013
DOI: 10.1002/pssc.201200383
|View full text |Cite
|
Sign up to set email alerts
|

Dominant mechanisms of electron scattering in ultra‐dilute GaAsN

Abstract: The dominant electron scattering mechanisms in GaAsN were investigated by analysing the Hall electron mobility and photoluminescence (PL) spectrum. The GaAsN thin films were grown by chemical beam epitaxy. The temperature dependence of the electron mobility indicated that polar optical phonon (POP) scattering was dominant in GaAs and GaAs:N0.0003 near room temperature. By increasing nitrogen compositions up to around 0.1%, the temperature dependence of the electron mobility became from T‐1.23 to T‐0.5. It indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…24,25 Additional effects of alloying such as potential fluctuations of the CBE caused by local variation of strain or composition (l / T À0.5 ) are probably less significant in the temperature range studies. This is also suggested by the work of Inagaki et al 26 They investigated ultra-dilute GaN x As 1Àx (x < 0.2%) and found that the CBE fluctuations alone could not explain the reduction of the electron mobility in the temperature range from 250 K to 400 K.…”
mentioning
confidence: 74%
“…24,25 Additional effects of alloying such as potential fluctuations of the CBE caused by local variation of strain or composition (l / T À0.5 ) are probably less significant in the temperature range studies. This is also suggested by the work of Inagaki et al 26 They investigated ultra-dilute GaN x As 1Àx (x < 0.2%) and found that the CBE fluctuations alone could not explain the reduction of the electron mobility in the temperature range from 250 K to 400 K.…”
mentioning
confidence: 74%
“…where e is the electron charge, µ e = 300 cm 2 Vs −1 , and µ hh = 50 cm 2 Vs −1 [81][82][83][84][85][86] are the electron, light hole and heavy hole mobilities. In contrast to equation ( 2), the exact Drude expression for the longitudinal conductivity contain magnetic field-dependent terms.…”
Section: Photoluminescence and Pcmentioning
confidence: 99%